The San Gregorio Magno lacustrine basin (Campania, southern Italy): improved characterization of the tephrostratigraphic markers based on trace elements and isotopic data. (18th July 2019) - Petrosino, P.; Arienzo, I.; Mazzeo, F. C.; Natale, J.; Petrelli, M.; Milia, A.; Perugini, D.; D′Antonio, M.
ABSTRACT: Central–southern Italy is one of the most suitable areas in the world for tephrostratigraphic studies, owing to the numerous volcanic sources with explosive activity during the Pleistocene. This work presents a systematic investigation of the chemical (trace elements) and isotopic (Sr and Nd) compositions of the main tephra markers within lacustrine sediments of the San Gregorio Magno Basin (Campania, southern Italy). This study: (i) provides full geochemical (trace elements and isotopes) characterization of eight significant Upper Pleistocene marker layers (X‐6, X‐5, C‐22, MEGT/Y‐7, CI/Y‐5, C‐10, Y‐3, NYT/C2) widely dispersed over the Mediterranean area; (ii) proposes a new tephra marker for Marine Isotope Stage 7, dated to 240 ka; and (iii) refines the correlations of tephra levels belonging to the investigated sequence. This study highlights that in most cases the Nd isotope composition of the glass and Sr isotope composition of the coexisting minerals are more reliable than 87 Sr/ 86 Sr of the glass, and hence is more helpful as a further tool for tephrostratigraphic correlations, as recently proposed in the literature. Moreover, this study is a first step towards the construction of a complete geochemical database for future tephra investigations in the Mediterranean area. Copyright © 2019 John Wiley & Sons, Ltd.